Effect of atypical rainfall on lotic zooplankton: Comparing downstream of a reservoir and tributaries with free stretches - Perbiche-Neves, Gilmar [UNESP]; Serafim, Moacyr Jr.; Portinho, Jorge Laço [UNESP]; Shimabukuro, Érika M. [UNESP]; Ghidini, André R.; de Brito, Lineu (My University, 2012)
To contribute to the knowledge of lotic zooplankton from dammed and free stretches, we tested the hypothesis that the ecological attributes are different between these environments, which are subjected to several effects caused by different hydrological conditions. The study was carried out in the low Iguaçu river, a large hydrographic basin in the south of Brasil. Two samplings were performed, one in the dry period (April/04) and the other in the atypical rainy period (July/04), in five stations downstream a large reservoir, and other 12 stations in four tributaries representing the upper, intermediate and low regions of each river. The observations suggest a clear spatial distribution of zooplankton in lotic stretches subjected or not to damming, mainly due to the effects of physical, chemical and biological variables. Furthermore, the atypical rainfall promoted alterations in community structure when compared to the dry period. © International Society for Tropical Ecology.
Keywords: Cladocera; Copepoda; Iguaçu river; Reservoir; Rotifera; Tributaries